Evidential Constructions as Deictic Markers of a Communicative Subject in Newspaper Political Narrative - Milostivaya, Alexandra (Research in Language, 2021)
The article is dedicated to studying communicative and pragmatic evidential constructions in newspaper political narrative. Based on the assumption that a communicative subject is represented as chain cooperation (“orderer” – editor – journalist – source – journalist), markers of evidentiality are matched with reference to the information about the events described on behalf of the source of relevant information. Correlation between an evidential discourse marker and an indication of the source of information in the narrative, as well as the possibility of indirect deictic reference to second-hand information with the help of modal verbs and lexical markers have been identified. Using evidential constructions in newspapers is determined pragmatically and connected with the narrator’s desire to distance him- or herself from unreliable or axiologically negative factors.